The effect of gamma-irradiation on graphene oxide in a monoglyceride/ethanol solution - Luu , Anh Tuyen; Ha , Thuc Huy; Nguyen , Thanh Duoc; Doan , Binh; Pham Thi , Thu Hong (Nuclear Science and Technology, 2016)
Gamma-irradiation effects on graphene oxide (GO) in a monoglyceride/ethanol (MG/EtOH) solution was investigated. GO was dispersed in MG/EtOH solution (GOM) with the GO: MG ratio of 1:10 (w/w). The prepared GOM was irradiated by g-ray under nitrogen atmosphere in a range of absorbed dose from 0 to 50 kGy. The characteristics and morphology of reduced GOM were analyzed by Ultraviolet-visible (UV-vis) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM). The results confirmed that the structure of reduced graphene oxide in monoglyceride solution was changed and exfoliated completely after g-ray irradiation at absorbed dose 50 kGy compared with non-irradiation sample.